Literasi Keuangan, Toleransi Risiko, dan Pengelolaan Keuangan Pelaku Usaha Mikro - Heni Hirawati; Yacobo P Sijabat; Axel Giovanni (Society, 2021)
Micro-enterprises have a significant role in the country’s economy. However, business owners must face various problems to develop their business. One of the problems is the limited funding for micro-enterprises due to the low financial literacy of business owners. In addition, the business owner’s tolerance for risk is also expected to affect the financial management of micro-enterprises. This study aims to determine the level of financial literacy and tolerance of business owners and the financial management of micro-enterprises. This research method uses a questionnaire distributed to micro-enterprise owners in Central Java Province and Yogyakarta Special Region. The results showed that the level of financial literacy of micro-enterprise owners was in the medium category. Micro-enterprise owners have a neutral attitude towards risk and are not individuals who dare to take risks but do not avoid risk. Financial management carried out by business owners is still in the poor category. Improvement of financial literacy, understanding of risks, and financial management of micro-enterprises still need to be done.